Exact solution for couple stress fluid flow past a fluid sphere embedded in a porous medium with slip condition - Kumar , M. Phani; Parasa, Dr. Naga Lakshmi Devi; Kunche, Dr Vijaya lakshmi (Journal of Naval Architecture and Marine Engineering, 2024)
In this paper, using interfacial slip on the boundary, the exact solution is obtained for the Stokes flow through a couple stress fluid sphere which is embedded (implanted) in a porous medium. Analytical computations are derived for the stream functions and drag. For the drag force, special conditions are deduced that satisfy the literature's facts. Graphs are created and the numerical results are tabulated. It is noticed that in the external viscous fluid case the porosity parameter and the drag coefficient are directly correlated and for the external couple stress fluid case with raises in slip parameter the coefficient of drag reduces. Journal of Naval Architecture and Marine Engineering, 21 (1), 2024, pp. 41–50